Modified Decision Feedback Equalizers for Nonlinearity Compensation in Coherent PAM4 Transmission System - Zhengxuan Li; Zheng Xin; Siyu Luo; Acai Tan; Bingyao Cao (Photonics)
To address chromatic dispersion (CD) and nonlinear impairments in coherent optical four-level pulse amplitude modulation (PAM4) systems, we propose a magnitude-assisted decision feedback equalizer (MA-DFE). The proposed scheme utilizes signal amplitude information to construct the error function, which is robust to carrier phase noise. Therefore, no additional carrier phase recovery operation is required during digital signal processing (DSP). Under conditions without CD pre-compensation, MA-DFE achieves 80 Gb/s single-wavelength transmission over a 25 km standard single-mode fiber (SSMF) in the C-band. When considering a bit error rate (BER) of 1 × 10−2 for the soft decision threshold, the link budget achieves 27 dB. In addition, we incorporate the phase into the error function, proposing the phase-assisted decision feedback equalizer (PA-DFE). PA-DFE is also unaffected by carrier phase noise and demonstrates better performance than MA-DFE when equalizing the more severe signal impairments caused by SOA gain saturation. Ultimately, we achieve a link budget of 29 dB using PA-DFE.